A quality improvement initiative for patient knowledge comprehension during the discharge procedure using a novel computer-generated patient-tailored discharge document in cardiology. (September 2022) - de Wit, André; de Heide, John; Cummins, Paul; van Bruchem-van de Scheur, Ada; Bhagwandien, Rohit; Lenzen, Mattie
Objective: The duration of hospital admissions has shortened significantly. This challenges healthcare professionals to provide the necessary information and instructions in a limited time. Patient-tailored discharge information may improve the patient's understanding of the discharge information but may also be time-consuming. The objective of this descriptive quality improvement study was to evaluate patient comprehension of discharge information using a novel computer-generated patient-tailored discharge document. Methods: A prospective pre-post study comparing patient-tailored discharge information with conventional discharge information, for patients undergoing an electrophysiological procedure during two periods of six weeks between January and March 2016. Group I received conventional discharge information ( n = 55). Group II received a computer-generated, patient-tailored discharge document ( n = 57). Their comprehension of the discharge information was evaluated using a peer-reviewed questionnaire distributed among patients, comparing groups I and II using Likert scales. Nurses and nurse practitioners evaluated the use of personalized discharge information by means of a short survey. Results: In terms of discharge information, comprehensibility was equivalent; however, an increase in comprehension was observed in patients seeking a telephone consultation with the cardiology department within one-week post-discharge. A reduction in discharge preparation time and an increased uniformity of discharge information were reported by nurses. Nurse practitioners found the web tool easy to use and time-saving. Conclusions: In this study, computer-generated patient-tailored discharge information was equivalent to conventional discharge information. A more positive trend was seen for patients who initiated teleconsultation with the hospital within one-week post-discharge. This suggests that for this subgroup the patient-tailored discharge web tool might lead to an improvement in care. However, more research with a larger number of participants is needed to confirm this trend.